2020
DOI: 10.3390/pathogens9070576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Genetic Diversity of Toxoplasma gondii Oocysts in Cat Faeces from Klang Valley, Malaysia, Using B1 and REP Genes in 2018

Abstract: The major route for Toxoplasma gondii (T. gondii) infection is through the ingestion of foods contaminated with oocyst from cat faeces. The microscopic detection of T. gondii oocysts in cat faeces is challenging, which contributes to the failure of detecting or differentiating it from other related coccidian parasites. This study aims to detect T. gondii oocysts in cat faeces using two multicopy-target PCR assays and to evaluate their genetic diversity. Cat faecal (200) samples were collected from pet cats (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 70 publications
1
7
2
Order By: Relevance
“…For example, the prevalence of T. gondii in stray cats in Tehran (15.2%), compared to other molecular studies in Iran, was higher than the previous prevalence reported in Mashhad (4.5%) ( 25 ) and Ahvaz (7.2%)( 26 ), and lower than the prevalence (24.1%) reported in Shiraz ( 27 ). Furthermore, compared to other molecular studies in the world, it is higher than the previous prevalence reported in South Korea (4.7% and 1.3%) ( 28 , 29 ), the USA (2%) ( 30 ), and Malaysia (13%)( 31 ), and lower than the prevalence reported in South Korea (17.5% and 30.6%)( 32 , 33 ) and Pakistan (34%)( 34 ). In addition, the prevalence of T. gondii infection in household cats in the current study (18.2%) was higher than the prevalence reported in Switzerland (0.58%) ( 35 ), Poland (2.4%) ( 36 ), Malaysia (4%) ( 31 ), Thailand (4.7%) ( 37 ) and Kenya (7.8%) ( 38 ), and lower than reported from Italy (20.5%) ( 39 ).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…For example, the prevalence of T. gondii in stray cats in Tehran (15.2%), compared to other molecular studies in Iran, was higher than the previous prevalence reported in Mashhad (4.5%) ( 25 ) and Ahvaz (7.2%)( 26 ), and lower than the prevalence (24.1%) reported in Shiraz ( 27 ). Furthermore, compared to other molecular studies in the world, it is higher than the previous prevalence reported in South Korea (4.7% and 1.3%) ( 28 , 29 ), the USA (2%) ( 30 ), and Malaysia (13%)( 31 ), and lower than the prevalence reported in South Korea (17.5% and 30.6%)( 32 , 33 ) and Pakistan (34%)( 34 ). In addition, the prevalence of T. gondii infection in household cats in the current study (18.2%) was higher than the prevalence reported in Switzerland (0.58%) ( 35 ), Poland (2.4%) ( 36 ), Malaysia (4%) ( 31 ), Thailand (4.7%) ( 37 ) and Kenya (7.8%) ( 38 ), and lower than reported from Italy (20.5%) ( 39 ).…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, compared to other molecular studies in the world, it is higher than the previous prevalence reported in South Korea (4.7% and 1.3%) ( 28 , 29 ), the USA (2%) ( 30 ), and Malaysia (13%)( 31 ), and lower than the prevalence reported in South Korea (17.5% and 30.6%)( 32 , 33 ) and Pakistan (34%)( 34 ). In addition, the prevalence of T. gondii infection in household cats in the current study (18.2%) was higher than the prevalence reported in Switzerland (0.58%) ( 35 ), Poland (2.4%) ( 36 ), Malaysia (4%) ( 31 ), Thailand (4.7%) ( 37 ) and Kenya (7.8%) ( 38 ), and lower than reported from Italy (20.5%) ( 39 ). To the best of our knowledge, this is the first study performed on the molecular prevalence of T. gondii infection in cat owners worldwide.…”
Section: Discussioncontrasting
confidence: 68%
“…All cat feces were collected daily and the production of oocysts was monitored by microscopic examination and PCR using T. gondii-specific target genes (529 bp repetitive sequence and B1 gene). Oocyst DNA was extracted from cat feces using the QIAamp Fast DNA Stool Mini Kit (Qiagen, Hilden, Germany) as previously described [21]. Two sets of T. gondii specific primers (Supplementary Table S1) were used in separate PCR reactions [22].…”
Section: In Vivo Infection Assay and Examination Of Toxoplasma Oocystsmentioning
confidence: 99%
“…Toxoplasma gondii is an important obligate intracellular apicomplexan zoonotic protozoa that causes toxoplasmosis in humans and other warm blooded animals worldwide (Wana et al, 2020a;Matta et al, 2021). Like other protozoan species, T. gondii has three infectious stages including oocysts, bradyzoites and tachyzoites (Waldman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%